2022
DOI: 10.3389/fspor.2022.949429
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying CrossFit®: Potential solutions for monitoring multimodal workloads and identifying training targets

Abstract: The design of high-intensity functional training (HIFT; e. g., CrossFit®) workouts and targeted physiological trait(s) vary on any given training day, week, or cycle. Daily workouts are typically comprised of different modality and exercise combinations that are prescribed across a wide range of intensities and durations. The only consistent aspect appears to be the common instruction to maximize effort and workout density by either completing “as many repetitions as possible” within a time limit (e.g., AMRAP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Such efforts may ultimately prove to be redundant and unnecessary. Recently, it was suggested that relationships might exist amongst workouts and/or workout components (e.g., the pull-up component of “Fran”) [ 21 ]. If true, workout components or entire workouts might be classified, and normative scores may only be necessary for symbolic representations of workout types or classifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such efforts may ultimately prove to be redundant and unnecessary. Recently, it was suggested that relationships might exist amongst workouts and/or workout components (e.g., the pull-up component of “Fran”) [ 21 ]. If true, workout components or entire workouts might be classified, and normative scores may only be necessary for symbolic representations of workout types or classifications.…”
Section: Discussionmentioning
confidence: 99%
“…In each instance, the modified workout typically programmed variants of Rx exercises, prescribed different repetition counts (per exercise), and/or different intensity loads when applicable [ 3 ]. Because these differences alter the assigned workload, equating different CrossFit ® -style workouts is inherently difficult [ 21 ], and verifying modified workloads may not be possible, only Rx performances were considered for this study. Cases were also excluded if the reported age was not between 18 and 54 years due to the lack of clarity on the leaderboard about which workout version these athletes completed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts may ultimately prove to be redundant and unnecessary. Recently, it was suggested that relationships might exist amongst workout and/or workout components (e.g., the pull-up component of "Fran") [21]. If true, workout components or entire workouts might be classified, and normative scores may only be necessary for symbolic representations of workout types or classifications.…”
Section: Discussionmentioning
confidence: 99%
“…Within the realm of research, there exist inquiries aimed at scrutinising the immediate impacts of these training configurations ( Gómez-Landero and Frías-Menacho, 2020 ), with a particular emphasis on factors such as fatigue levels associated with these methodologies ( De-Oliveira et al, 2022 ). Despite the difficulty in defining and controlling the training stimulus, given the variable characteristics of the programs ( Mangine and Seay, 2022 ), we will focus on the strength exercises that are usually part of these programs. In this regard, the vast majority of the studies analyse the effects on similar absolute loads or, failing that, relative loads established with respect to the value of 1RM ( Maté-Muñoz et al, 2018 ; Silva-Grigoletto et al, 2020 ; De-Oliveira et al, 2021 ; De-Oliveira et al, 2022 ), which can present serious limitations ( Sanchez-Medina and González-Badillo, 2011 ; Elvar-Heredia et al, 2021 ; Maté-Muñoz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%